Boundary and Space : an Introduction to the Work of D.W. Winnicott. - Davis, Madeleine (Karnac Books, 1991)
This book provides a systematic presentation of D.W. Winnicott's developmental and clinical methodology. It includes a comprehensive bibliography of the works from which the book draws and an enlightening aricle that links Winnicott's evolving ideas to various stages of his life.